PENGGUNAAN METODE JARITMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN DI KELAS IA SD INPRES MAUMERE - Maria Salome (Jurnal Akrab Juara, 2019)
Mathematics is something that is related to abstract ideas / concepts arranged hierarchically through deductive reasoning. The aim of Mathematics learning is focused on mastering the concept of counting and memorizing skills based on the facts in the field. For that Mathematics is taught to students with the aim that students are able to solve problems in daily life by counting. The skill of counting multiplication as part of Mathematics is very much needed by humans in various aspects of life. In the Mathematics learning Material Addition and Subtraction in class IA SD Inpres Maumere, a decrease in student learning outcomes was found. This is because many of the students consider Mathematics as a difficult subject, so their learning enthusiasm decreases. Therefore, researchers use the Jarithmetic method as an effort to make Mathematics lessons fun and students can improve their learning outcomes